Formalne związki między powinnością a dobrem. Rozważania na marginesie prac Henryka Elzenberga - Drofiszyn, Marcin (Filozofia Nauki, 2020)
The paper presents a relative preference semantics for multimodal logic of good and ought inspired by the axiological writings of Henryk Elzenberg. Its central concept is the act of preference between alternative possibilities performed by a metaempirical will, guided only by pure reasons. In semantics, the act of a metaempirical will is modeled using an orderly relation between possible worlds. Using this logic, I formalize some relationships between good and ought posited by Elzenberg.